Land Tenure, Investment Incentives, and the Choice of Techniques - Bandiera, Oriana (World Bank, 2012)
Land Tenure, Investment Incentives, and the Choice of Techniques: Evidence from Nicaragua Oriana Bandiera The choice of cultivation techniques is a key determinant of agricultural productivity and has important consequences for income growth and poverty reduction in developing countries. Further evidence indicates that the result follows from landlords' inability or unwillingness to commit to long-term tenancy contracts rather than from agency costs due to risk aversion or limited liability. This finding is in line with the observation that since a tenant's effort affects tree productivity in the future, proper incentives can be provided only by offering a long-term contract that makes the tenant's pay conditional on future output. Nevertheless, models of moral hazard with either risk aversion or limited liability indicate that tenants' wealth determines the cost of providing incentives for noncontractible effort and hence the choice of cultivation techniques when these are complementary to effort. To this purpose, the remainder of the 496 THE WORLD BANK ECONOMIC REVIEW analysis focuses on the cross-sectional evidence from the sample of pure owners and pure tenants. Cross-Section Specification: Matching Estimates Nonexperimental matching procedures might yield estimates that improve over linear regression estimates in the sense of being closer to those produced by a randomized experiment. Land Ownership and Trees: Linear Probability Model Fixed-Effect and Cross-Section Estimates Cross-section Fixed effects Tree mix Variable Farmer owns plot Household wealth*1026 Farmer's age Farmer's gender Farmer's education (years) Household size Farm size*1023 Plot size*1023 Town size*1026 Average distance to market town Percent increase in probability when moving from tenancy to ownership Province fixed effect Number of observations (farmers) R2 No 86 0.08 29 Yes 1172 0.02 2668 (1.25) 0.354 (0.228 The results also show that trees are more likely to be grown on smaller farms, which rules out the hypothesis that there are increasing returns to scale to tree cultivation and that the observed difference between owners and tenants is due to the fact that owners farm larger plots. Observations are matched on the same farmer and town characteristics used in table 3 Source: Author's analysis based on data from the 1998 Nicaragua Living Standards Measurement Study survey. Since poorer tenants are more likely to be risk averse (Binswanger 1980) and because the limited-liability constraint is more likely to be binding for poor tenants, models of risk aversion or limited liability share the prediction that tenants' wealth determines the cost of providing incentives and hence effort and the choice of production techniques.